SISTEM DESELERASI KECEPATAN OTOMATIS PADA MOBIL BERDASARKAN JARAK MENGGUNAKAN SENSOR ULTRASONIK HC-SR04 BERBASIS ARDUINO MEGA 2560 - Musthofa, Fikri; Winarno, Heru (Gema Teknologi, 2015)
Fikri Musthofa, Heru Winarno, in this paper explain that along with the high number of accidents on the highway at this time of course must be a special concern for motorists. There are many factors that underlie the occurrence of an accident in driving, the most important of which is the factor of driver error in driving, such as drowsiness or lack of rest, lack of concentration, and much more. Besides the security system in vehicles is also very influential in reducing the number of accidents in driving. With the development of today's technology, it is necessary to create a speed deceleration system on the motor based on the distance to the barrier objects in front of the vehicle using ultrasonic sensors. Ultrasonic sensor which is a type of proximity sensor is a sensor that can detect distances so that it can be used as a sensor in this system. This system can reduce motor speed automatically when the sensor detects a barrier object in front with a distance of less than 300 cm. This system will be active when the ultrasonic sensor detects a distance of less than 300 cm. At that distance the Arduino Mega 2560 will adjust the PWM value of the motor, the motor PWM value will decrease 12% every second so that within a period of 8 seconds the motor will have a speed of 0 rpm which means the motor will stop. This system is expected to reduce the number of road accidents due to motorists' faults.Â Keywords: Speed Deceleration, PWM Method, Ultrasonic Sensor, Arduino Mega 2650.ReferencesAgus Setya Abadi, Delta. 2008. Sensor Ultrasonic Sebagai Alat Navigasi Robot Pemadam Api.. Tugas Akhir PSD III Teknik Elektro (Tidak diterbitkan) Semarang : Universitas Diponegoro.Anonimus. 2012. Sensor Ultrasonic HC-SR04. Diunduh dari http://arduino- learning.com/code/hc-sr04-ultrasonic-sensor-example.php diakses pada 1 Juni 2015 pukul 14.30 WIB.Anonimus. 2013. Rangkaian Skematik Driver Motor L298N. Diunduh dari http://www.yujum.com/rangkaian-dan-skematik-driver-motor-l298n/ diakses pada 17 Juni 2015 pukul 19.45.Anonimus. 2014. Accumulator atau Aki dan jenisnya. Diunduh dari http://www.sandielektronik.com/2014/03/accumulator-atau-aki.html diakses pada 30 Mei 2015 pukul 16.15 WIB.Prayogo, Rudito. 2012. Pengaturan PWM dengan PLC. Tugas Mata Kuliah Teknik Otomasi (Tidak diterbitkan). Malang: Universitas Brawijaya.Riny Sulistyowati. 2012. Perancangan Prototype System Kontrol Dan Monitoring Pembatas Daya Listrik Berbasis Mikrokontroler. Surabaya : Institut Adhi Tama Surabaya.Surono. 1988. Tata Tulis Karya Ilmiah Bahasa Indonesia. Semarang : Fakultas Sastra Universitas Diponegoro.